Complement activation and anaphylactoid response to protamine in a child after cardiopulmonary bypass. Issue 5 (May 1985) - Westaby, S; Turner, M W; Stark, J
Abstract : A 2 1/2 year old boy had a sudden, severe, and unexpected anaphylactoid reaction after an otherwise uncomplicated repair of a partial atrioventricular septal defect. The reaction, comprising haemorrhagic pulmonary oedema and peripheral circulatory collapse, followed neutralisation of heparin by protamine. Measurements of serum complement (C3 and C4) concentrations suggested that a pronounced consumption of complement occurred during the adverse response.